Microsurgical Composite Tissue Transplantation at Difficult Recipient Sites Facilitated by Preliminary Installation of Vein Grafts as Arteriovenous Loops - Ritter, Edmond F.; Anthony, James P.; Levin, L. Scott; Demas, Christopher P.; Klitzman, Bruce; Skarada, Doug; Serafin, Donald (Journal of Reconstructive Microsurgery, 1996)
In microvascular surgery when local recipient vessels are inadequate, vein grafting is required. There are several potential inherent disadvantages of immediate vein grafting, including the development of graft thrombosis or leakage, an increased opportunity for technical errors, and an increased number of anastomoses in series. All of these may contribute to a higher failure rate for composite-tissue transplantation requiring vein grafts. The authors hypothesized that in cases where vein grafting is obviously required, the creation of a temporary, looped, arteriovenous fistula (AVF) would reduce the morbidity of vein grafting, by allowing the detection of thrombosis or technical errors predisposing to thrombosis prior to free-tissue transplantation. Since delaying the division of an AVF for 5 or more days may allow time for healing of the endothelium at the AVF anastomotic site, the hypothesis was that composite-tissue transplantation whose vein grafts were installed as an AVF divided in a delayed manner, might have better patency than those in which vein grafts were installed at the time of reconstruction.This study reviews the results of 16 patients (8 females, 8 males) who underwent 17 microvascular reconstructions using AVFs. Patient courses and outcomes were compared between those undergoing immediate (8 patients) and delayed (7 patients) AVF construction, division, and free-tissue transplantation. There was a low patency rate for AVFs which were divided in a delayed fashion (2 of 7 patients, 29 percent), compared with those which were immediately divided (10 of 10, 100 percent). These results suggest that, in spite of a strong theoretical basis for delayed division of the AVF, delayed harvesting of the AVF is empirically associated with a higher thrombosis rate (p = 0.0048, Fishers exact test).